Penerapan Media Clay Color Bahan Alami dalam Menstimulasi Perkembangan Motorik Halus Anak Usia Dini di TK As Sakinah Majalengka - Isfa Annaissatul Ula; Andri Hardiyana; Eti Nurhayati (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2023)
The problem in this study is the lack of fine motor development in early childhood at the As Sakinah Majalengka Kindergarten so that it has not reached the expected achievement indicators. It is characterized by a lack of interesting learning. Therefore, when learning children always feel bored. So one of the solutions is to apply a natural material clay color medium to stimulate fine motor skills in early childhood at the As Sakinah Kindergarten Majalengka. This study aims to find out how the development of fine motor skills in early childhood at As Sakinah Majalengka Kindergarten. The method used in this research is descriptive qualitative method. The data collection technique was through observations made in early childhood, while the informants in the interviews were 2 people consisting of the school principal and the As Sakinah Majalengka Kindergarten class teacher. Data analysis techniques used include data collection, data reduction, data presentation and conclusion. The results showed that the application of clay color media in the development of fine motor skills of early childhood in the Kindergarten As Sakinah Majalengka has been going well. The fine motor skills of group A children in Kindergarten As Sakinah Majalengka, namely meeting the criteria of Developing According to Expectations (BSH) are included in the Very Good category. It can be seen that by applying clay color media, children's fine motor development is well developed. Then the child becomes more enthusiastic about learning because by using clay media learning related to fine motor skills is more varied and interesting so that children's fine motor development develops as expected. The child's response to the application of this clay media is that the child is so enthusiastic and eager to play while learning.